Three Years of Community Projects - Planning Commission (Planning Commission, 1956)
According to the quarterly report of the Project for the period ending September 1955 all the villages (247) in the Project are covered by development activities. But the term development activities has been used in such a wide sense as to include even magic lantern shows and meetings held. Information is not available in respect of coverage of villages by programmes in fields such as agriculture and health. As for community works it is stated that construction of school buildings appears to be widespread and undertaken in as many as 95 out of 247 villages.
Government of India Planning Commission Programme Evaluation Organisation